A Study on the perception of medical students using online teaching during covid -19 pandemic - Anita Kumari; Sudha Rani; Mary Pushpa Bara (Journal of Family Medicine and Primary Care, 2022)
Introduction: COVID-19 has caused unprecedented disruption to the medical education process and the health care system worldwide. It has also affected clinical training and forced medical colleges to switch over to the online mode of teaching. This study aimed to learn about the experience and perception of undergraduate students regarding online learning and to study the advantage and disadvantages of online learning. Method: This was a cross-section study conducted among the undergraduate students of government medical colleges of Jharkhand. A validated electronic questionnaire was sent to students of all five government medical colleges in the google form. Response from 501 students was received and analyzed using SPSS software. Result: Only 30% of students were satisfied with the frequency, organization content, and preparedness of class. More than half of students were not satisfied with the preparedness, content, and frequency of online classes. Among various teaching methods, live online lectures were most common, and they were also preferred by the majority of students. Most of the students wanted a regular face-to-face classroom or hybrid teaching after the COVID-19 pandemic. Conclusion: The majority of the medical students preferred face-to-face teaching methods over online teaching methods. Lack of interpersonal interaction and poor infrastructure for online might be the reason for this. However, a hybrid method of learning can be included as a part of the medical curriculum that helps in better learning of medical students.